Dampak Sosial Ekonomi Zakat di Masyarakat Indonesia - Aldakhil, Muhammad Rizqy (Maliki Interdisciplinary Journal, 2024)
Zakat is one of the main pillars of Islam which has great potential to improve the social and economic welfare of the community. society. This article discusses how zakat affects the social and social and economic life in Indonesia by providing real examples and data and showing that zakat can help reduce poverty, increase demonstrates that zakat can help reduce poverty, improve welfare and support economic needs or identifies some of the challenges in the management of zakat in Indonesia. Zakat distribution can boost economic growth. The greater the zakat funds distributed, the greater the economic growth. Zakat payments can generate a multiplier effect in the economy, indirectly benefiting the community. Zakat in the form of consumer assistance alone already has a significant multiplier effect, but if it is provided in the form of productive assistance, such as business capital, it will have an even greater multiplier effect.